2018
DOI: 10.1007/s13197-018-3431-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of ohmic heating for concentration of milk

Abstract: The concentration of milk through evaporation is the most commonly employed unit operation for the production of a wide array of traditional and industrial dairy products. Major problems associated with thermal evaporation are a loss of aroma, flavor and color change. Ohmic heating (OH) has an immense potential for rapid and uniform heating of liquid, semi-solid and particulate foods, yielding microbiologically safe and high-quality product. The effect of ohmic heating on physico-chemical, rheological, sensori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 24 publications
3
27
0
Order By: Relevance
“…It was determined that Ohmic heating assisted evaporation (OHAE) process on milk and dairy product are limited (Parmar et al, 2018).…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was determined that Ohmic heating assisted evaporation (OHAE) process on milk and dairy product are limited (Parmar et al, 2018).…”
Section: Practical Applicationsmentioning
confidence: 99%
“…In the study, milk samples (cow, buffalo, and mixed milk) were evaporated to 25% total soluble solid content at 13.3 V/cm and quality properties were evaluated (Parmar et al, 2018). However, with the knowledge of the authors, no evaluation of EC and exergy analysis studies with Ohmic heating evaporation of milk and dairy products was found.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Microwaves, radiofrequency, high pressure, pulsed electric fields and ultrasound are some examples. Among the emergent technologies, ohmic heating (OH) has been extensively researched in recent years (Cappato et al, 2018;Gally et al, 2017;Parmar, Singh, Meena, Borad, & Raju, 2018;Silva, Santos, & Silva, 2017).…”
Section: Emergent Technologies For Microbial Inactivation -Ohmic Heatingmentioning
confidence: 99%
“…Lack of knowledge about different types of electrodes on energy loss. (Icier & Ilicali, 2005;Parmar et al (2018)…”
Section: Solution Concentrationmentioning
confidence: 99%
“…As the traditional concentration methods may negatively affect the physicochemical properties of milk, researchers are exploring the applicability of emerging technologies for milk concentration to produce a high‐quality product (Faion et al, 2019; Moejes, vanWonderen, Bitter, & vanBoxtel, 2020; Parmar, Singh, Meena, Borad, & Raju, 2018). The refractance window (RW) is a novel food processing technique that is believed to produce high‐quality products and has been used for drying food material at both laboratory and industrial scales (Bernaert, VanDroogenbroeck, VanPamel, & DeRuyck, 2019; Jafari, Azizi, Mirzaei, & Dehnad, 2016; Raghavi, Moses, & Anandharamakrishnan, 2018).…”
Section: Introductionmentioning
confidence: 99%